Positive electrode pre-sodium composite current collector and preparation method and application thereof
By filling the positive electrode pre-sodium additive with high dissociation potential in the porous current collector and coating the conductive carbon layer on the surface, the problems of sodium ion batteries in the first charge and discharge efficiency, short cycle life, and low energy density are solved, and safe and controllable sodium supplementation is achieved, which significantly improves the performance of the battery.
Patent Information
- Application Number
- CN202411881577.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Existing sodium ion batteries have problems with low first charge and discharge efficiency, short cycle life, low energy density, etc., and the traditional sodium supplementation method has complex operation, strict environmental requirements, and great safety hazards.
A positive electrode pre-sodium composite liquid collector is adopted to achieve safe and controllable sodium supplementation by filling the positive electrode pre-sodium additive with high dissociation potential in the porous current collector and coating a conductive carbon layer on the surface.
It significantly improves the battery's first charge and discharge efficiency and energy density, extends the cycle life, and improves the battery's safety performance.
Smart Images

Figure CN119695166A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of sodium ion battery materials, and in particular to a positive electrode pre-sodium composite current collector. Background Art
[0002] Low-cost, long-life, highly safe and controllable large-scale energy storage systems are necessary requirements for achieving sustainable development needs of modern society and meeting carbon peak and carbon neutrality. With the rapid development of large-scale electrochemical energy storage systems, the global demand for lithium resources has increased, and a supply shortage has occurred. In addition, my country has relatively few lithium resource reserves, and 85% relies on imports. It is of far-reaching significance to find a new type of battery that can replace lithium-ion batteries. Sodium-ion batteries and lithium-ion batteries have similar mechanisms, the same equipment, and compatible production lines. They are regarded as secondary batteries that may be commercialized on a large scale. However, there are still many problems in the actual application of batteries, such as low initial charge and discharge efficiency, short cycle life, and low energy density. Sodium can be supplemented through the positive or negative electrode to improve its electrical performance. Traditional sodium supplementation and lithium supplementation are similar, and are divided into electrochemical sodium supplementation, chemical sodium supplementation, and additive sodium supplementation. Electrochemically, the electrode is pre-treated to replenish sodium, and then reassembled into a battery. This method is complicated to operate, increases the production process and cost, and is rarely used in commercial technology routes; chemical sodium replenishment, such as the application with publication number CN 115050968 A, is achieved by compounding active sodium powder or sodium foil on the negative electrode. This method has strict environmental requirements, has safety hazards, and the amount of sodium replenishment and the reaction process are difficult to control; additive sodium replenishment is achieved by adding a sodium replenisher to the positive electrode side. Common examples include patent application CN 118039844 A, which directly adds a pre-sodium additive to the positive electrode slurry. Because the pre-sodium agent is mostly a non-conductive material and occupies a certain proportion in the slurry, it will undoubtedly increase the impedance of the electrode material layer, reduce the proportion of active materials, and cannot control the reaction. Therefore, a better pre-sodium method is urgently needed to solve the bottleneck of existing technologies. Summary of the invention
[0003] In order to solve the above technical problems and realize safe and controllable sodium supplementation, the present invention proposes a positive electrode pre-sodium composite current collector and a preparation method and application thereof.
[0004] To achieve the above object, the technical solution of the present invention is implemented as follows:
[0005] A positive electrode pre-sodium composite current collector comprises a porous current collector, a positive electrode pre-sodium filling layer filled in the pores of the porous current collector, and a conductive carbon layer located on the surface of the current collector; wherein the positive electrode pre-sodium filling layer comprises a positive electrode pre-sodium additive; the positive electrode pre-sodium additive is at least one of Na2C2O4, Na2C6O6, Na4C6O6, NaN3, Na2S, Na2CO3 and Na3P.
[0006] The present invention fills a positive electrode pre-sodium additive (at least one of Na2C2O4, Na2C6O6, Na4C6O6, NaN3, Na2S, Na2CO3 and Na3P) with a dissociation potential higher than 3.65V and gas generation under high temperature into a porous current collector, and after drying and rolling, a conductive carbon layer is coated on the surface to prepare a highly safe and controllable positive electrode pre-sodium composite current collector. When it is applied to a sodium ion battery, on the one hand, according to actual needs, by increasing the charging cut-off potential in real time and intermittently, the filling layer releases sodium ions to supplement the irreversible sodium source loss in the battery, which can meet the sodium supplementation in the whole life cycle of the battery, significantly improve the battery's first efficiency and energy density, and at the same time increase the battery's cycle life; on the other hand, before the battery has a safety hazard, the pre-sodium agent is heated to generate gas, so that the current collector and the material layer are separated, and the failure deterioration is prevented in time, thereby improving the safety performance of the battery. In addition, the conductive carbon layer plays a role in buffering and reducing interfacial tension, which is conducive to the later coating of the positive electrode active material on the composite current collector.
[0007] The positive electrode pre-sodium filling layer also includes a binder, conductive carbon and an additive; the conductive carbon layer includes conductive carbon and a binder.
[0008] Furthermore, the above-mentioned positive electrode pre-sodium filling layer includes 70wt%-96wt% of positive electrode pre-sodium additive, 1wt%-10wt% binder, 2wt%-10wt% conductive carbon and 1wt%-10wt% auxiliary agent; the conductive carbon layer includes 90wt%-98wt% conductive carbon and 2wt%-10wt% binder.
[0009] The binder is at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyacrylamide, polyacrylamide and hydroxyethyl cellulose; the conductive carbon is at least one of carbon black, conductive graphite, carbon nanotubes, graphene and acetylene black.
[0010] The auxiliary agent is at least one of polyvinyl pyrrolidone, dipropylene glycol, polyethylene glycol, triglycerol and decaglycerol.
[0011] The porous current collector is aluminum foil or PET aluminum foil with a thickness of 5-50 μm and a pore size of 1-100 μm; the thickness of the conductive carbon layer is 0.05 μm-20 μm.
[0012] A method for preparing a positive electrode pre-sodium composite current collector, comprising the following steps:
[0013] (1) Adding a binder into a solvent and stirring to prepare a glue solution;
[0014] (2) dry-mixing the positive electrode pre-sodium additive and the conductive carbon, adding the glue solution and the auxiliary agent prepared in step (1) and stirring to obtain slurry I; filling the slurry into the pores of the porous current collector, baking and rolling to obtain a porous current collector containing a positive electrode pre-sodium filling layer;
[0015] (3) Add conductive carbon to the glue solution obtained in step (1), stir evenly to obtain slurry II, and apply it to the porous current collector obtained in step (2) by scraping or spraying to obtain a positive electrode pre-sodium composite current collector.
[0016] Furthermore, the solvent is at least one of N-methylpyrrolidone, tetramethyl urea, trimethyl phosphate and dimethyl sulfoxide; and the thickness of the positive electrode pre-sodium filling layer is not greater than the thickness of the porous current collector.
[0017] Furthermore, the viscosity of the above slurry I is 1000-9000 mPa·s; the viscosity of slurry II is 4000-20000 mPa·s.
[0018] Specifically, the preparation method of the above-mentioned positive electrode pre-sodium composite current collector comprises the following steps:
[0019] 1. The positive electrode pre-sodium filling layer is filled in the porous current collector
[0020] S1. At room temperature of 25°C, add the binder to the solvent and stir for 6-12 hours to prepare a transparent adhesive solution with a solid content of 1%-10%. Take it out and set aside.
[0021] S2. The positive electrode pre-sodium additive and the conductive carbon are dry mixed in a certain proportion for 0.5h-3h, and the homogenizer is rotated at 20-40 rpm and 500-2000 rpm to make the charge and discharge mix uniformly;
[0022] S3. Add the prepared glue and additives in sequence, maintain revolution at 30-50 rpm, rotation at 3000-5000 rpm, and stir for 3-6h;
[0023] S4. Adjust the viscosity of the slurry to 1000-9000 mPa·s and uniformly fill the pores of the porous current collector.
[0024] 2. Preparation of porous current collector containing positive electrode pre-sodium filling layer
[0025] The positive electrode sodium supplement additive is filled in the porous current collector, and then dried and rolled to obtain the product, wherein the drying temperature is 25°C-60°C.
[0026] 3. Preparation of Conductive Carbon Layer
[0027] S1. At room temperature 25°C, add the binder into the solvent and stir for 6-12 hours to prepare a transparent adhesive solution.
[0028] S2. Add conductive carbon in multiple steps, maintain revolution at 40-70 rpm, rotation at 4000-8000 rpm, and stir for 6-10h;
[0029] S3. Adjust the viscosity of the slurry to 4000-20000 mPa·s and apply it onto the current collector by scraping or spraying.
[0030] A sodium ion battery comprises the above-mentioned positive electrode pre-sodium composite current collector.
[0031] The beneficial effects produced by the present invention are:
[0032] (1) The present invention provides a positive electrode pre-sodium composite current collector, which is different from the traditional method of directly mixing the pre-sodium agent into the active material slurry by filling the pre-sodium agent into the porous current collector. This pre-sodium method is aimed at the traditional method, does not increase the electrode impedance, and does not reduce the proportion of active materials. It is simple to operate, friendly to environmental requirements, controllable in real time, simple to operate, and easy to engineer.
[0033] (2) The present invention preferably uses an organic or inorganic sodium salt (at least one of Na2C2O4, Na2C6O6, Na4C6O6, NaN3, Na2S, Na2CO3 and Na3P) with a dissociation potential higher than 3.65V as a positive electrode pre-sodium additive, which does not dissociate under normal battery operating voltage. According to actual needs, the charging cut-off voltage can be intermittently increased, the charging current and charging time can be controlled to release sodium ions and replenish the irreversibly lost sodium source, thereby achieving controllable sodium replenishment throughout the life cycle.
[0034] (3) The positive electrode pre-sodium additive of the present invention will generate gas when heated at high temperature, forcing the current collector and the coating layer to separate, which can form a short circuit in time, slow down or avoid failure deterioration, and improve battery safety performance.
[0035] (4) The present invention fills the positive electrode pre-sodium additive into the porous current collector, which can improve the battery's initial charge and discharge efficiency, energy density and cycle life.
[0036] (5) The conductive carbon layer in the present invention has good sodium ion / electron conduction channels, kinetics and structural stability, plays a buffering role between the filling layer and the subsequent active material layer, and improves the interface of the current collector after filling, which is convenient for the subsequent active material coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 SEM image of the positive electrode pre-sodium composite current collector prepared in Example 1 of the present invention.
[0039] Figure 2This is a charging curve of a sodium ion battery prepared with the positive electrode pre-sodium composite current collector of Example 1 and charged to 4.2V.
[0040] Figure 3 This is the normal discharge curve of the sodium ion battery prepared with the positive electrode pre-sodium composite current collector of Example 1.
[0041] Figure 4 This is the normal discharge curve of the sodium ion battery prepared with the positive electrode pre-sodium composite current collector of Example 2.
[0042] Figure 5 This is the normal discharge curve of the sodium ion battery prepared with the positive electrode pre-sodium composite current collector of Example 3.
[0043] Figure 6 This is the normal discharge curve of the sodium ion battery prepared with the positive electrode pre-sodium composite current collector of Example 4.
[0044] Figure 7 This is the normal discharge curve of the sodium ion battery prepared with the positive electrode pre-sodium composite current collector of Example 5.
[0045] Figure 8 This is the normal discharge curve of the sodium ion battery prepared with the positive electrode pre-sodium composite current collector of Example 6.
[0046] Fig. 9 This is the normal discharge curve of the sodium ion battery prepared with the positive electrode pre-sodium composite current collector of Example 7.
[0047] Fig.10 The graph is a curve of the number of cycles and capacity of a sodium ion battery prepared with the positive electrode pre-sodium composite current collector of Example 1 after 500 cycles of pre-sodium and continued cyclic charge and discharge.
[0048] Fig.11 This is the normal discharge curve of the sodium ion battery prepared with the composite current collector of Comparative Example 1.
[0049] Implementation method
[0050] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] Example 1
[0052] A preparation method of a positive electrode pre-sodium composite current collector of this embodiment includes three stages. The first stage is to fill the pre-sodium additive into the porous current collector, the second stage is to bake and roll the current collector after filling, and the third stage is to coat the surface with a conductive carbon layer. The specific steps are as follows:
[0053] Stage 1: Pre-sodium additives are filled into the porous current collector
[0054] (1) At room temperature (25°C), 10 wt% of the binder polyvinylidene fluoride (444.4 g) was weighed and dissolved in 4 L of N-methylpyrrolidone solvent, and stirred for 12 h to prepare a transparent adhesive solution with a solid content of 10%. The adhesive solution was taken out and set aside;
[0055] (2) 70 wt% positive electrode pre-sodium additive Na2C2O4 (3111.11 g) and 10 wt% conductive agent carbon nanotubes (444.4 g) were dry mixed for 3 h, and the homogenizer was kept at 40 revolutions / min and 2000 revolutions / min to ensure that the charge and discharge mixing was uniform;
[0056] (3) Add the prepared glue solution and 10 wt% auxiliary agent polyvinyl pyrrolidone (444.4 g) in sequence, maintain the revolution at 50 rpm and the rotation at 5000 rpm, and stir for 6 h;
[0057] (4) The slurry viscosity was adjusted to 1000 mPa·s and the slurry was uniformly filled in a porous aluminum foil current collector with a thickness of 12 μm and a pore size of 50 μm. The thickness of the pre-sodium filling layer was 12 μm.
[0058] Phase II: Preparation of porous current collector containing positive electrode pre-sodium filling layer
[0059] After drying at 45° C. and roller pressing, a positive electrode pre-sodium composite current collector precursor (a porous current collector containing a positive electrode pre-sodium filling layer) with a flat surface is obtained;
[0060] The third stage: preparation of the surface conductive carbon layer
[0061] (1) At room temperature (25°C), 2 wt% of a binder (40 g of polyvinylidene fluoride) was added to 2 L of N-methylpyrrolidone solvent and stirred for 12 h to prepare a transparent adhesive solution.
[0062] (2) adding 98 wt% conductive agent carbon black (1960 g) in multiple steps, maintaining the revolution at 70 rpm and the rotation at 8000 rpm, and stirring for 10 h;
[0063] (3) adjusting the slurry viscosity to 10000 mPa·s and spraying it onto the current collector;
[0064] (4) The thickness of the conductive carbon coating is 1 μm, and finally a positive electrode pre-sodium composite current collector is obtained.
[0065] The SEM image of the positive electrode pre-sodium composite current collector prepared in this embodiment is as follows: Figure 1 As shown, from Figure 1 It can be seen that the coating surface is smooth and the conductive agent is evenly distributed.
[0066] Example 2
[0067] A preparation method of a positive electrode pre-sodium composite current collector of this embodiment includes three stages. The first stage is to fill the pre-sodium additive into the porous current collector, the second stage is to bake and roll the current collector after filling, and the third stage is to coat the surface with a conductive carbon layer. The specific steps are as follows:
[0068] Stage 1: Pre-sodium additives are filled into the porous current collector
[0069] (1) At room temperature (25°C), 5 wt% of the binder polyvinylidene fluoride (210.5 g) was weighed and dissolved in 4 L of N-methylpyrrolidone solvent and stirred for 6 h to prepare a transparent adhesive solution with a solid content of 5%. The adhesive solution was taken out and set aside;
[0070] (2) 85 wt% positive electrode pre-sodium additive Na2C6O6 (3578.9 g) and 5 wt% conductive agent carbon nanotubes (210.5 g) were dry mixed for 0.5 h, and the homogenizer was kept rotating at 20 rpm and 500 rpm to ensure that the charge and discharge mixing was uniform;
[0071] (3) Add the prepared glue solution and 5 wt% auxiliary agent polyvinyl pyrrolidone (210.5 g) in sequence, maintain the revolution at 50 rpm and the rotation at 5000 rpm, and stir for 6 h;
[0072] (4) The slurry viscosity was adjusted to 9000 mPa·s and the slurry was uniformly filled in a porous aluminum foil current collector with a thickness of 12 μm and a pore size of 50 μm. The thickness of the pre-sodium filling layer was 6 μm.
[0073] Phase II: Preparation of porous current collector containing positive electrode pre-sodium filling layer
[0074] After drying at 60° C. and roller pressing, a positive electrode pre-sodium composite current collector precursor (a porous current collector containing a positive electrode pre-sodium filling layer) with a flat surface is obtained;
[0075] The third stage: preparation of the surface conductive carbon layer
[0076] (1) At room temperature (25°C), 4 wt% of a binder (80 g of polyvinylidene fluoride) was added to 2 L of N-methylpyrrolidone solvent and stirred for 6 h to prepare a transparent adhesive solution.
[0077] (2) adding 96 wt% conductive agent carbon black (1920 g) in multiple steps, maintaining the revolution at 40 rpm and the rotation at 4000 rpm, and stirring for 6 h;
[0078] (3) Adjust the slurry viscosity to 20000 mPa·s and spray it onto the current collector;
[0079] (4) The thickness of the conductive carbon coating is 5 μm, and finally a positive electrode pre-sodium composite current collector is obtained.
[0080] Example 3
[0081] A preparation method of a positive electrode pre-sodium composite current collector of this embodiment includes three stages. The first stage is to fill the pre-sodium additive into the porous current collector, the second stage is to bake and roll the current collector after filling, and the third stage is to coat the surface with a conductive carbon layer. The specific steps are as follows:
[0082] Stage 1: Pre-sodium additives are filled into the porous current collector
[0083] (1) At room temperature (25°C), 1 wt% of the binder polyvinylidene fluoride (40.4 g) was weighed and dissolved in 4 L of N-methylpyrrolidone solvent and stirred for 6 h to prepare a transparent adhesive solution with a solid content of 1%. The adhesive solution was taken out and set aside;
[0084] (2) 96 wt% of the positive electrode pre-sodium additive Na2S (3878.8 g) and 2 wt% of the conductive agent carbon nanotubes (80.8 g) were dry mixed for 0.5 h, and the homogenizer was kept rotating at 20 rpm and 500 rpm to ensure that the charge and discharge mixing was uniform;
[0085] (3) Add the prepared glue solution and 1 wt% auxiliary agent polyvinyl pyrrolidone (40.4 g) in sequence, maintain the revolution at 30 rpm and the rotation at 3000 rpm, and stir for 3 h;
[0086] (4) The slurry viscosity was adjusted to 9000 mPa·s and the slurry was uniformly filled in a porous aluminum foil current collector with a thickness of 12 μm and a pore size of 50 μm. The thickness of the pre-sodium filling layer was 12 μm.
[0087] Phase II: Preparation of porous current collector containing positive electrode pre-sodium filling layer
[0088] After drying at 60° C. and roller pressing, a positive electrode pre-sodium composite current collector precursor (a porous current collector containing a positive electrode pre-sodium filling layer) with a flat surface is obtained;
[0089] The third stage: preparation of the surface conductive carbon layer
[0090] (1) At room temperature (25°C), 2 wt% of a binder (40 g of polyvinylidene fluoride) was added to 2 L of N-methylpyrrolidone solvent and stirred for 6 h to prepare a transparent adhesive solution.
[0091] (2) adding 98 wt% of conductive carbon black (1960 g) in multiple steps, maintaining the revolution at 40 rpm and the rotation at 4000 rpm, and stirring for 6 h;
[0092] (3) Adjust the slurry viscosity to 20000 mPa·s and spray it onto the current collector;
[0093] (4) The thickness of the conductive carbon coating is 5 μm, and finally a positive electrode pre-sodium composite current collector is obtained.
[0094] Example 4
[0095] The method for preparing a positive electrode pre-sodium composite current collector in this embodiment is different from that in Example 1 in that the positive electrode pre-sodium additive is Na4C6O6, and the remaining steps are the same.
[0096] Example 5
[0097] The method for preparing a positive electrode pre-sodium composite current collector in this embodiment is different from that in Example 1 in that the positive electrode pre-sodium additive is NaN3, and the remaining steps are the same.
[0098] Example 6
[0099] The method for preparing a positive electrode pre-sodium composite current collector in this embodiment is different from that in Example 1 in that the positive electrode pre-sodium additive is Na2CO3, and the remaining steps are the same.
[0100] Example 7
[0101] The method for preparing a positive electrode pre-sodium composite current collector in this embodiment is different from that in Example 1 in that the positive electrode pre-sodium additive is Na3P, and the remaining steps are the same.
[0102] Example 8
[0103] A method for preparing a positive electrode pre-sodium composite current collector in this embodiment comprises the following steps:
[0104] Stage 1: Pre-sodium additives are filled into the porous current collector
[0105] (1) At room temperature (25°C), 8 wt% of the binder polyvinylidene fluoride (347.8 g) was weighed and dissolved in 4 L of N-methylpyrrolidone solvent, and stirred for 8 h to prepare a transparent adhesive solution with a solid content of 8%. The adhesive solution was taken out and set aside;
[0106] (2) 72 wt% positive electrode pre-sodium additive Na2C2O4 (3130.4 g) and 10 wt% conductive agent conductive graphite (434.8 g) were dry mixed for 1.5 h, and the homogenizer was kept rotating at 30 rpm and 1000 rpm to ensure that the charge and discharge were evenly mixed;
[0107] (3) Add the prepared glue solution and 10 wt% auxiliary agent polyvinyl pyrrolidone (434.8 g) in sequence, maintain the revolution at 40 rpm and the rotation at 4000 rpm, and stir for 4.5 h;
[0108] (4) The slurry viscosity was adjusted to 4000 mPa·s and the slurry was uniformly filled in a porous PET aluminum foil current collector with a thickness of 50 μm and a pore size of 1 μm. The thickness of the pre-sodium filling layer was 50 μm.
[0109] Phase II: Preparation of porous current collector containing positive electrode pre-sodium filling layer
[0110] After natural drying at 25° C. and roller pressing, a positive electrode pre-sodium composite current collector precursor (a porous current collector containing a positive electrode pre-sodium filling layer) with a flat surface is obtained;
[0111] The third stage: preparation of the surface conductive carbon layer
[0112] (1) At room temperature (25°C), 10 wt% of a binder (200 g of polyvinylidene fluoride) was added to 2 L of N-methylpyrrolidone solvent and stirred for 7 h to prepare a transparent adhesive solution.
[0113] (2) adding 90 wt % conductive graphite (1800 g) in multiple steps, maintaining the revolution at 50 rpm and the rotation at 6000 rpm, and stirring for 8 h;
[0114] (3) Adjust the slurry viscosity to 4000 mPa·s and apply it onto the current collector by scraping;
[0115] (4) The thickness of the conductive carbon coating is 20 μm, and finally a positive electrode pre-sodium composite current collector is obtained.
[0116] Example 9
[0117] A method for preparing a positive electrode pre-sodium composite current collector in this embodiment comprises the following steps:
[0118] Stage 1: Pre-sodium additives are filled into the porous current collector
[0119] (1) At room temperature (25°C), 8 wt% of the binder polyvinylidene fluoride (347.8 g) was weighed and dissolved in 4 L of N-methylpyrrolidone solvent, and stirred for 8 h to prepare a transparent adhesive solution with a solid content of 8%. The adhesive solution was taken out and set aside;
[0120] (2) 80 wt% of the positive electrode pre-sodium additive Na2C2O4 (3478 g) and 8 wt% of the conductive agent acetylene black (347.8 g) were dry mixed for 1.5 h, and the homogenizer was kept rotating at 30 rpm and 1000 rpm to ensure that the mixture was evenly charged and discharged;
[0121] (3) Add the prepared glue solution and 4 wt% auxiliary agent polyvinyl pyrrolidone (173.9 g) in sequence, maintain the revolution at 40 rpm and the rotation at 4000 rpm, and stir for 4.5 h;
[0122] (4) The slurry viscosity was adjusted to 6000 mPa·s and the slurry was uniformly filled in a porous PET aluminum foil current collector with a thickness of 5 μm and a pore size of 100 μm. The thickness of the pre-sodium filling layer was 5 μm.
[0123] Phase II: Preparation of porous current collector containing positive electrode pre-sodium filling layer
[0124] After natural drying at 25° C. and roller pressing, a positive electrode pre-sodium composite current collector precursor (a porous current collector containing a positive electrode pre-sodium filling layer) with a flat surface is obtained;
[0125] The third stage: preparation of the surface conductive carbon layer
[0126] (1) At room temperature (25°C), 5 wt% of a binder (100 g of polyvinylidene fluoride) was added to 2 L of N-methylpyrrolidone solvent and stirred for 7 h to prepare a transparent adhesive solution.
[0127] (2) adding 95 wt % conductive graphite (1900 g) in multiple steps, maintaining the revolution at 50 rpm and the rotation at 6000 rpm, and stirring for 8 h;
[0128] (3) Adjust the slurry viscosity to 4000 mPa·s and apply it onto the current collector by scraping;
[0129] (4) The thickness of the conductive carbon coating is 0.05 μm, and finally a positive electrode pre-sodium composite current collector is obtained.
[0130] Comparative Example 1
[0131] In this comparative example, carbon-coated aluminum foil is used as the current collector, the base aluminum foil is a 12 μm foil, and the conductive carbon-coated layer is a 5 μm graphene. The specific preparation method is as follows:
[0132] (1) At room temperature (25°C), 2 wt% of a binder (40 g of polyvinylidene fluoride) was added to 2 L of N-methylpyrrolidone solvent and stirred for 6 h to prepare a transparent adhesive solution.
[0133] (2) adding 98 wt% conductive agent carbon black (1960 g) in multiple steps, maintaining the revolution at 40 rpm and the rotation at 4000 rpm, and stirring for 6 h;
[0134] (3) Adjust the slurry viscosity to 20000 mPa·s and spray it onto the current collector;
[0135] (4) The thickness of the conductive carbon coating is 5 μm, and a composite current collector is finally obtained.
[0136] Application Examples
[0137] The positive electrode pre-sodium composite current collectors prepared in Examples 1-7 and the composite current collectors prepared in Comparative Example 1 were applied to sodium ion batteries, wherein the specific preparation method of the sodium ion battery is as follows:
[0138] (1) Preparation of positive electrode sheet: N-methylpyrrolidone (NMP) and polyvinylidene fluoride (PVDF) were prepared into a glue solution for use. The polyanion positive electrode material and conductive carbon black (SP) were dry-mixed and then added into multi-walled carbon nanotube (CNT) slurry and glue solution step by step. The proportion of each component was NFM111: PVDF: SP: CNT = 96: 2: 1.5: 0.5. The mixture was stirred at high speed for 120 min, vacuumed to remove bubbles, sieved, and discharged. The single-surface density was 15 mg / cm 2 Coating onto a positive electrode pre-sodium composite current collector or a composite current collector to prepare a positive electrode sheet;
[0139] (2) Preparation of negative electrode sheet: Sodium carboxymethyl cellulose (CMC) was added to water to prepare a glue solution for use. Hard carbon and conductive carbon black (SP) were dry-mixed and then added with single-walled carbon nanotube (CNT) slurry and glue solution step by step. The mixture was stirred at high speed for 180 min, and then vacuumed to remove bubbles. After adjusting the viscosity, styrene-butadiene rubber (SBR) was added. The proportion of each component was hard carbon: SP: CNT: CMC: SBR = 91.2: 2.5: 0.05: 2.5: 3.75. The mixture was stirred slowly for 30 min, sieved, and discharged. The mixture was coated on copper foil at an N / P ratio of 1.15, corresponding to a single-sided surface density of 8.38 mg / cm 2 , preparing a negative electrode sheet;
[0140] (3) Battery assembly: The positive and negative electrodes are pressed to 1.9 g / cm 3 , 1g / cm 3 The finished battery cells are prepared through roller pressing, followed by die cutting, baking, lamination, hot pressing, tab welding, packaging, secondary baking, liquid injection, aging, and formation.
[0141] The sodium ion battery prepared in the above-mentioned manner was subjected to electrochemical performance testing. The sodium ion battery prepared in Example 1 needs to be pre-charged with sodium before normal discharge, wherein the purpose of pre-charging with sodium is to replenish the sodium source lost in the formation of the SEI film; the sodium ion battery prepared in Comparative Example 1 is directly charged and discharged normally.
[0142] (1) Use a step-by-step current to perform normal discharge after pre-sodium, the specific steps are as follows:
[0143] a. Charge the battery to 4.2V in a step-by-step current manner; b. Discharge it to 2.0V; c. Then charge the battery normally to 3.65V; d. Discharge it to 2.0V.
[0144] Figure 2 When the positive electrode pre-sodium composite current collector prepared in Example 1 is applied to a sodium ion battery, the battery is charged to 4.2V. As can be seen from the figure, there is a small platform for the dissociation of the pre-sodium additive when it is higher than 3.65V and close to 4.0V, indicating that the sodium source is released at this stage.
[0145] Figure 3 This is the normal discharge curve of the positive electrode pre-sodium composite current collector prepared in Example 1 applied to a sodium ion battery. It can be seen that the first cycle discharge capacity is 5.9 Ah.
[0146] Figure 4 This is the normal discharge curve of the positive electrode pre-sodium composite current collector prepared in Example 2 applied to a sodium ion battery. It can be seen that the first cycle discharge capacity is 5.802Ah.
[0147] Figure 5 This is the normal discharge curve of the positive electrode pre-sodium composite current collector prepared in Example 3 applied to a sodium ion battery. It can be seen that the first cycle discharge capacity is 5.888Ah.
[0148] Figure 6 This is the normal discharge curve of the positive electrode pre-sodium composite current collector prepared in Example 4 applied to a sodium ion battery. It can be seen that the first cycle discharge capacity is 5.84Ah.
[0149] Figure 7 This is the normal discharge curve of the positive electrode pre-sodium composite current collector prepared in Example 5 applied to a sodium ion battery. It can be seen that the first cycle discharge capacity is 5.828Ah.
[0150] Figure 8 This is the normal discharge curve of the positive electrode pre-sodium composite current collector prepared in Example 6 applied to a sodium ion battery. It can be seen that the first cycle discharge capacity is 5.884Ah.
[0151] Fig. 9 This is the normal discharge curve of the positive electrode pre-sodium composite current collector prepared in Example 7 applied to a sodium ion battery. It can be seen that the first cycle discharge capacity is 5.861Ah.
[0152] Fig.10 When the positive electrode pre-sodium composite current collector prepared in Example 1 is applied to a sodium ion battery, the battery can release the sodium source in a controllable manner by increasing the charge cut-off voltage to 4.2 V when the battery is cycled for 500 cycles, thereby improving the cycle life. This further illustrates that during the use of the battery, sodium ions can be released at any time to supplement sodium by simply increasing the charge voltage, which reflects the controllable feature.
[0153] (2) The sodium ion battery prepared in the comparative example is discharged normally, and the specific process is as follows:
[0154] a. Charge the battery normally to 3.65V; b. Discharge it to 2.0V. Fig.11 This is a normal discharge curve of a sodium ion battery using the composite current collector prepared in Comparative Example 1. It can be seen that the first cycle discharge capacity is 5.561 Ah.
[0155] The results of the discharge capacity, initial charge and discharge efficiency and energy density of different embodiments and comparative examples are shown in Table 1.
[0156] Table 1
[0157] Group Discharge capacity / Ah First charge and discharge efficiency % Energy densityWh / Kg Example 1 5.90 85.5 127.3 Example 2 5.802 84.1 125.1 Example 3 5.888 85.3 127.0 Example 4 5.84 84.6 126.0 Example 5 5.828 84.4 125.7 Example 6 5.884 85.2 127 Example 7 5.861 84.9 126.4 Comparative Example 1 5.561 80.6 119.9
[0158] It can be seen from Table 1 that the present invention fills the positive electrode pre-sodium additive into the porous current collector, and the battery's initial charge and discharge efficiency and energy density can be improved by pre-sodium treatment.
[0159] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A positive electrode pre-sodium composite current collector, characterized in that The positive electrode pre-sodium composite current collector includes a porous current collector, a positive electrode pre-sodium filling layer filled in the pores of the porous current collector, and a conductive carbon layer located on the surface of the current collector; wherein the positive electrode pre-sodium filling layer includes a positive electrode pre-sodium additive; the positive electrode pre-sodium additive is at least one of Na2C2O4, Na2C6O6, Na4C6O6, NaN3, Na2S, Na2CO3 and Na3P.
2. The positive electrode pre-sodium composite current collector according to claim 1, characterized in that The positive electrode pre-sodium filling layer also includes a binder, conductive carbon and an auxiliary agent; the conductive carbon layer includes conductive carbon and a binder.
3. The positive electrode pre-sodium composite current collector according to claim 2, characterized in that: The positive electrode pre-sodium filling layer includes 70wt%-96wt% of a positive electrode pre-sodium additive, 1wt%-10wt% of a binder, 2wt%-10wt% of conductive carbon and 1wt%-10wt% of an auxiliary agent; the conductive carbon layer includes 90wt%-98wt% of conductive carbon and 2wt%-10wt% of a binder.
4. The positive electrode pre-sodium composite current collector according to claim 2 or 3, characterized in that: The binder is at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyacrylamide, polyacrylamide and hydroxyethyl cellulose; the conductive carbon is at least one of carbon black, conductive graphite, carbon nanotubes, graphene and acetylene black.
5. The positive electrode pre-sodium composite current collector according to claim 4, characterized in that: The auxiliary agent is at least one of polyvinyl pyrrolidone, dipropylene glycol, polyethylene glycol, triglycerol and decaglycerol.
6. The positive electrode pre-sodium composite current collector according to claim 5, characterized in that: The porous current collector is aluminum foil or PET aluminum foil with a thickness of 5-50 μm and a pore size of 1-100 μm; the thickness of the conductive carbon layer is 0.05 μm-20 μm.
7. A method for preparing a positive electrode pre-sodium composite current collector as claimed in claim 1, characterized in that: The steps are: (1) Add the binder into the solvent and stir to prepare a glue solution; (2) dry-mixing the positive electrode pre-sodium additive and the conductive carbon, adding the glue solution and the auxiliary agent prepared in step (1) and stirring to obtain slurry I; filling the slurry I into the pores of the porous current collector, baking and rolling to obtain a porous current collector containing a positive electrode pre-sodium filling layer; (3) Add conductive carbon to the slurry obtained in step (1), stir evenly to obtain slurry II, and apply it onto the porous current collector obtained in step (2) by scraping or spraying to obtain a positive electrode pre-sodium composite current collector.
8. The method for preparing the positive electrode pre-sodium composite current collector according to claim 7, characterized in that: The solvent is at least one of N-methylpyrrolidone, tetramethyl urea, trimethyl phosphate and dimethyl sulfoxide; the thickness of the positive electrode pre-sodium filling layer is not greater than the thickness of the porous current collector.
9. The method for preparing the positive electrode pre-sodium composite current collector according to claim 8, characterized in that: The viscosity of the slurry I is 1000-9000 mPa·s; the viscosity of the slurry II is 4000-20000 mPa·s.
10. A sodium ion battery, characterized in that: It includes the positive electrode pre-sodium composite current collector as described in claim 1.
Citation Information
Patent Citations
Lithium-supplementing current collector, preparation method and application thereof, negative pole piece and lithium ion battery
CN111430723A
High-capacity porous current collector pre-sodium sodium ion battery composite negative electrode and preparation method thereof
CN115050968A
Lithium supplement positive electrode current collector, preparation method and battery
CN117039001A
Sodium-ion battery positive electrode pre-sodium-modified pole piece and preparation method thereof
CN117673252A
Secondary battery and electric equipment
CN117996231A